(untitled) (Agroindustrial Science, 2025)
Structural composition of bread crumb, as well as its volume, are important factors in fresh bread characterization. ImageJ was used as a digital technique to evaluate the morphometry, color, and alveolar constitution in crumb. Wheat bread was made with partial replacement of papaya seed flour in percentages ranging from 5% to 30%. Morphometric analysis allowed characterizing the circularity (between 0.8433 ± 0.00 and 0.8833 ± 0.01), radius aspect (between 1.03 ± 0.01 and 1.10 ± 0.01), and roundness (between 0.9000 ± 0.02 and 0.9700 ± 0.01), which were not statistically significant (p < 0.05). However, the alveolar count was higher in the control (399.00 ± 66.09), compared to bread added with papaya seed flour (155.33 ± 23.71-211.00 ± 158.07). When color determining, values showed tendencies towards red with maximum values in control treatment with 214.83 ± 23.32 pixels. In dimensions values, a decrease in these was observed, being affected by percentage increase in papaya seed flour. Therefore, papaya seed flour addition showed effects that can be evaluated using digital techniques as a non-invasive tool.